2018
DOI: 10.25134/ijbe.v1i1.1360
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance to Prevent Financial Distress Evidence from Corporate Governance Perceptions Index of Indonesian Companies

Abstract: This study aims to determine the influence of Good Corporate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This raises the question that constitutes the objective of this paper: Does corporate governance cure financial distress? In assessing this question, a look at extant literature showed that while some researchers (Adegbie, Akintoye, & Ashaolu, 2019;Ali, Liu, & Su, 2018;Ayoola & Obokoh, 2018;Martins & Junior, 2019;Manab, Aziz, & Othman, 2017;Miglani, Ahmed, & Henry, 2015;Witiastuti & Suryandari, 2016) argue that financial distress could be avoided if a firm implements good corporate governance strategy, others (Afrifa & Tauringana, 2015;Khan & Javid, 2016;Rahmawati & Handriyana, 2018) claim that compliance with corporate governance codes is not enough to prevent financial distress. A study by three Australian Professors of Accounting (Abernethy, Grafton, & Soderstrom, 2016) gave the following conclusions "while it may be true that a firm that scores highly on corporate governance measures is less likely to default in the future, we cannot say for certain that it avoided default because of these attributes" (p.8).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question that constitutes the objective of this paper: Does corporate governance cure financial distress? In assessing this question, a look at extant literature showed that while some researchers (Adegbie, Akintoye, & Ashaolu, 2019;Ali, Liu, & Su, 2018;Ayoola & Obokoh, 2018;Martins & Junior, 2019;Manab, Aziz, & Othman, 2017;Miglani, Ahmed, & Henry, 2015;Witiastuti & Suryandari, 2016) argue that financial distress could be avoided if a firm implements good corporate governance strategy, others (Afrifa & Tauringana, 2015;Khan & Javid, 2016;Rahmawati & Handriyana, 2018) claim that compliance with corporate governance codes is not enough to prevent financial distress. A study by three Australian Professors of Accounting (Abernethy, Grafton, & Soderstrom, 2016) gave the following conclusions "while it may be true that a firm that scores highly on corporate governance measures is less likely to default in the future, we cannot say for certain that it avoided default because of these attributes" (p.8).…”
Section: Introductionmentioning
confidence: 99%